Remineralizing efficacy of fluoride in the presence of oral microcosm biofilms. (December 2021) - Kang, Min-Kyung; Kim, Hee-Eun
Highlights: Evaluated the remineralizing efficacy of fluoride in the presence of oral microcosm biofilms. In vitro assessment conducted using pH-cycling model with oral microcosm biofilms. Oral biofilms significantly affect the remineralizing efficacy of fluoride. Oral biofilms present a considerable barrier to fluoride penetration. Oral biofilms must be considered when testing efficacy of remineralizing agents. Abstract: Objectives: The oral biofilm structure or composition can affect the penetration of remineralizing agents. Therefore, this study evaluated the remineralizing efficacy of fluoride using a pH-cycling model with oral microcosm biofilms. Methods: Artificial carious lesions were formed in 80 bovine incisors. The pH-cycling conditions with or without oral microcosm biofilms were applied to 40 specimens each. The pH-cycling scheme was repeated for 12 days. Fluorescence loss (ΔF, %) of early carious lesions was measured for all specimens using a quantitative light-induced fluorescence-digital camera, before and after fluoride application. Biofilms on specimens were further analyzed for red fluorescence intensity (red/green ratios) and colony-forming unit counts. The effects of pH-cycling conditions and treatments on changes in ΔF (ΔΔF) and the effects of interactions between factors were analyzed using two-way analysis of variance. Results: The fluoride-treated group with oral biofilms had an approximately 0.89-fold lower ΔΔF than the fluoride-treated group without oral biofilms ( p  < 0.0001). When oral biofilms were absent, the fluoride-treated group showed a 1.31-fold greater ΔΔF compared to that in the distilled water-treated group ( p  < 0.0001). When oral biofilms were present, the fluoride-treated group showed a 1.14-fold greater ΔΔF compared to that in the distilled water-treated group; however, this difference was not statistically significant. Conclusions: There was a significant difference in fluoride remineralizing efficacy based on the presence of biofilms on early carious lesions. Therefore, fluoride remineralization assessment in the absence of oral biofilms could lead to an overestimation of efficacy. Clinical Significance: Fluoride application might not have a robust remineralization effect on early carious lesions in the presence of a mature biofilm on the tooth surface. Graphical abstract: Image, graphical abstract